Impact of maternal neuraxial labor analgesia exposure on offspring's neurodevelopment: A longitudinal prospective cohort study with propensity score matching - Chun-Mei Deng; Ting Ding; Zhi-Hua Liu; Shu-Ting He; Jia-Hui Ma; Ming-Jun Xu; Lei Wang; Ming Li; Wei-Lan Liang; Xue-Ying Li; Daqing Ma; Dong-Xin Wang; et al. (Frontiers Media S.A., 2022)
BackgroundNeuraxial analgesia is widely used to relieve labor pain; its effects on long-term neurodevelopment of offspring remain unclear. This study was designed to investigate the influence of maternal neuraxial labor analgesia on offspring mental development.MethodsThis was a predefined secondary analysis of a 2-year prospective longitudinal study. Nulliparous women with single-term cephalic pregnancy preparing for vaginal delivery self-selected neuraxial analgesia or not during labor. Mothers and their offspring were followed up 2 years later. children's mental development was assessed with the bayley scales of infant development. A multivariable logistic model was used to identify factors associated with below-average mental development (Mental Development Index <90).ResultsA Total of 508 pairs of mothers and children completed a 2-year follow-up. after propensity score matching, 387 pairs were included in the analysis. In both cohorts, the proportions with below-average mental development were slightly lower in children whose mothers received neuraxial labor analgesia, although not statistically significant [in the full cohort: 9.8 % (36/368) vs. 15.7% (22/140), P = 0.060; In the matched cohort: 8.3% (21/254) vs. 14.3% (19/133), P = 0.065]. A higher 2-year depression score (in the full cohort: Odds Ratio 1.15, 95% CI 1.08-1.22, P < 0.001; In the matched cohort: Odds Ratio 1.09, 95% CI 1.01-1.18, P = 0.037), but not neuraxial analgesia exposure, was associated with an increased risk of below-average mental development.ConclusionsMaternal depression at 2 years was associated with the risk of below-average mental development, whereas maternal exposure to neuraxial labor analgesia was not.Clinical Trial RegistrationThe study was registered with www.chictr.org.cn (ChiCTR-OCH-14004888) and ClinicalTrials.gov (NCT02823418).